Efficiency Properties of Labor Taxation in a Spatial Model of Restricted Labor Mobility - Patrik Guggenberger; Ashok Kaul; Martin Kolmar (Institute for the Study of Labor (IZA), 2001)
We examine the efficiency properties of labor taxation. A spatial model of an economy is introduced whose key feature is a new approach to restricted labor mobility. We characterize the efficient allocation of labor and properties of a decentralized equilibrium. An efficient allocation of labor can be compatible with marginal productivity differentials stemming from binding mobility restrictions. We investigate two scenarios of labor taxation (firm-specific taxes and countryspecific taxes) and in both setups we give a complete characterization of the cases for which there is scope for redistribution without affecting effciency. Finally, we discuss the applicability of our model in the context of the place of employment and place of residence principle of taxation.
Keywords: H7; R5; J61; 330; Restricted Labor Mobility; Efficient Allocation of Labor; Labor Taxation; Lohnsteuer; Ursprungslandprinzip; Steuerwirkung; Arbeit; Allokationseffizienz; Räumliche Gleichgewichtstheorie; Internationale Arbeitsteilung; Internationale Arbeitsmobilität; Steuerwettbewerb; social planning model